Effect of Filler Loading on Mechanical and Tribological Properties of Wood Apple Shell Reinforced Epoxy Composite - Ojha Shakuntala; Gujjala Raghavendra; Acharya Samir Kumar (Advances in Materials Science and Engineering)
During the last century, natural fibers and particulates are used as reinforcement in polymer composite that has been continuously growing in the composite industry. This polymer matrix composite has wide range of applications in hostile environment where they are exposed to external attacks such as solid particle erosion. Also, the mechanical properties of different polymer composites show the best alternate to replace the metal material. In the present investigation, an attempt has been made to improve the mechanical and tribological behaviour of polymer matrix composite using wood apple shell particles as a filler material in polymer matrix. Also the temperature variation of the dynamic-mechanical parameters of epoxy matrix composites incorporated with 5, 10, 15, and 20 wt% of wood apple shell particles was investigated by DMA test. It is clearly observed that the incorporation of wood apple shell particles tends to increase the tensile strength, flexural strength, erosive wear resistance, and viscoelastic stiffness of the polymer composite. To validate the results, SEM of the polymer matrix composite has been studied.